THE TRAVELING SCIENCE TEACHER LECTURE-DEMONSTRATION PROGRAM. - Bowles, Joseph E.; Maben, Jerrold William; Dutton, F. B. (Science Education, 1962)
The article presents a reprint of a paper by Joseph E. Bowles, Jerrold William Maben, and F.B. Dutton of Michigan State University, which was presented at the at the 34th annual meeting of the National Association for Research in Science Teaching held February 24, 1961 in Chicago, Illinois. The authors discusses the Traveling Science Lecture-Demonstration program initiated in 1956 by the Oak Ridge Institute of Nuclear Studies in Tennessee.